OPTIMIZATION OF CUTTING FORCE DURING LATHE PROCESSING STEEL 40X - Saruulbold S.; Oyunbat G. (World Science, 2024)
One of the important parameters of the turning metal is the cutting force. This force is the force that occurs during the cutting process and is influenced by various factors, such as  tool wear, temperature in the target zone, and surface cleanliness. Cutting force has a significant influence on the cutting process. This paper presents a correlation between cutting force and turning procedure as a result of comparing experimental cutting force to the Advant Edge program’s result. Determining the main parameters  of turning procudere by the Minitab program were the turning speed V=157 m/min, feed s=0.12 mm/rev, depth t=1 mm, cutting  force Рz= 2.02 kN, Py=0.74 kN, and Px=1.77 kN.